O olhar queirosiano entre centro e periferia : "Os Ingleses no Egipto", Eça de Queirós (Gazeta de Notícias - 1882) - Pereira, Patrícia Ayres (2009)
Current investigation is a critical interpretation of non-fictional texts called Os ingleses no Egipto [The British in Egypt], written by the Portuguese author Eça de Queirós, and published in the 1882 edition of a Brazilian journal. The journalist Eça de Queirós wrote essays for the Gazeta de Notícias, perhaps one of the most influential 19th century newspapers in Rio de Janeiro, Brazil. Correspondence or journalistic texts give the reader a general view of culture, politics and society of the period, with its conflicting power relationships in the Britain- France-Egypt axis. The situation and conditions of Queirós's philosophy is analyzed under the aegis of Edward E, Said's concept of Orientalism, or rather, the system of knowledge on the relationships among countries featuring different types of politics, culture and economy. Further, Foucault's concepts are also employed when the relationships between discourse and power are taken into consideration. The relationship between the center and the margin, in this case, Britain and Egypt, is thus focused so that Queiros's critical and reflexive perspective may be revealed. The manner relationships are perceived and reported by the Portuguese journalist and citizen is also taken into account, especially when one considers Portugal, with its medium-sized economy, experiencing a semi-peripheral attitude, in the words of Boaventura de Sousa Santos, with Britain as the center. Queirós's non European and non Eurocentric attitude is thus revealed. Since the essays do not even reflect Portugal's philosophy, there is an ambiguous relationship with Europe, or rather, his relationship is identical to Portugal's semi-peripheral condition. Queirós uses a disruptive irony-based rhetoric so that the reader may have a clear idea of Egypt's woes and their causes: British economical interests. Although current research does not restrict itself to Queirós as a journalist, it focuses on 19th century thought by employing state-of-the-art theoretical approaches posterior to the Gazeta publications.